CKAP2L, a crucial target of miR-326, promotes prostate cancer progression - Qi Li; Mo Yan; Chunhui Wang; Kaibin Wang; Guochang Bao (BMC Cancer, 2022)
Abstract Background The overexpression of aberrant cell cycle signaling pathway associated protein has been implicated in multiple malignancies and the identification of all-important one among is the crux of the precise targeted therapy. CKAP2L (Cytoskeleton Associated Protein 2 Like) plays a newish role in cancer progression through activation of the process of cell cycle and mitosis. In this study, we aim to delineate the prominent dysregulated expression of CKAP2L and comprehensively reveal its deregulation in prostate cancer.  Method CKAP2L expression was examined in the normal and tumor tissues of prostate cancer patients with RT-QPCR and Western blot. IHC showed the different expression in normal prostate tissue, tissue of BPH, low Gleason Score and high Gleason Score prostate cancer patients. Transwell, colony formation, MTT and flow cytometry were performed to detected the changes in cellular function in vitro. The xenograft model was conducted for the changes in vivo. Dual luciferase and RIP proved the binding relation between CKAP2L and miR-326. Results In multiple datasets, CKAP2L was found upregulated and positively associated with Gleason grade and poor clinical outcomes of patients. shRNA mediated silence of CKAP2L suppressed cell proliferation, impaired monolayer formation, inhibited cell invasion. CKAP2L was confirmed to be the direct target of miR-326, which had a carcinostatic effect by binding the 3’untranslated regions (3’UTRs) of CKAP2L mRNA. The deletion of CKAP2L resulted in reduced expression of genes involved in the mitotic cell cycle such as multiple cyclin-dependent kinases and cyclins, but also several genes encoding proteins involved in chromosome segregation and spindle assembly. Conclusion Taken together, CKAP2L plays a carcinogenic role in prostate cancer by regulates the expression of cycle-associated proteins.